2020
DOI: 10.1002/aoc.6079
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antiprotozoal activities of silver coordination polymers derived from the asymmetric halogenated Schiff base ligands

Abstract: A series of polymeric silver(I) complexes with Schiff base ligands containing pyridine and 3,5‐halogen substituted phenol moieties were synthesized and characterized by spectroscopic methods and in the case of Ag6 also by X‐ray crystallography. All silver(I) complexes (Ag1–Ag8) were evaluated for their biological activity against a panel of pathogens including the protozoa Trypanosoma cruzi, T. brucei, T. rhodesiense and Leishmania infantum; the bacteria Staphylococcus aureus, Escherichia coli, Mycobacterium t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 97 publications
(126 reference statements)
0
9
0
Order By: Relevance
“…[32][33][34] Also, the introduction of halogens into the phenyl ring decreases drug metabolism. [35][36][37] Therefore, halogen bonding is a powerful tool to design more effective medicinal compounds for medicinal chemistry. For instance, it has been recently described that in a series of Pd (II) complexes with halogen-substituted Schiff bases and 2-picolylamine, the number and types of halogens influence not only the chirality but also their cytotoxicity towards breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Also, the introduction of halogens into the phenyl ring decreases drug metabolism. [35][36][37] Therefore, halogen bonding is a powerful tool to design more effective medicinal compounds for medicinal chemistry. For instance, it has been recently described that in a series of Pd (II) complexes with halogen-substituted Schiff bases and 2-picolylamine, the number and types of halogens influence not only the chirality but also their cytotoxicity towards breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to discrete metal complexes, some silver(I)-based coordination polymers represent improved stability and release properties, thus also gaining an impetus for applications in anticancer and antimicrobial treatment. 27 29 In particular, water-soluble cagelike aminophosphine ligands such as PTA (1,3,5-triaza-7-phosphaadamantane) and its various derivatives constitute an appealing class of linkers for designing bioactive coordination polymers. 30 − 32 Notable examples of such silver(I)-based compounds with potent and diverse bioactivity were reported in our previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to discrete metal complexes, some silver­(I)-based coordination polymers represent improved stability and release properties, thus also gaining an impetus for applications in anticancer and antimicrobial treatment. In particular, water-soluble cagelike aminophosphine ligands such as PTA (1,3,5-triaza-7-phospha­adamantane) and its various derivatives constitute an appealing class of linkers for designing bioactive coordination polymers. Notable examples of such silver­(I)-based compounds with potent and diverse bioactivity were reported in our previous studies. Within this context and following our major goal in exploring the chemistry and biofunctional applications of silver–PTA coordination polymers, herein we report the self-assembly synthesis, characterization, spectroscopic and structural features, and antiviral, antimicrobial, and antiproliferative properties of a new silver­(I) coordination polymer derived from PTA and quinolinic acid, [Ag­(Hquin)­(μ-PTA)] n ·H 2 O ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The supramolecular assembly between nanoGS and Pent was prepared at a 1:1 molar ratio using the classical method of organic film hydration ( Figure 4A ). In our study we employed Pent as a free base [ 19 , 26 ], slightly soluble in water (i.e., ≅30 µg/mL), instead of Pent isethionate salt used in the literature for the preparation of β-CD/Pent inclusion complex [ 27 28 ]. Specifically, De Paula et al described a deep inclusion of Pent into CD cavities and demonstrated the interactions of both aromatic and aliphatic chain protons of Pent with internal hydrogens of the cavity by NMR analyses.…”
Section: Resultsmentioning
confidence: 99%